Macro-modelling approach for assessment of out-of-plane behavior of brick masonry infill walls. (15th February 2019) - Pantò, B.; Silva, L.; Vasconcelos, G.; Lourenço, P.B.
Highlights: The out-plane response of brick infills is experimentally and numerically studied. Two unreinforced and steel reinforced brick masonry infill solutions are considered. An innovative discrete macro-modelling strategy is employed in the simulations. Parametric analyses identified the main system parameters influencing the response. Abstract: This paper deals with the numerical simulation of two solutions of brick infill walls developed at University of Minho under out-of-plane loading. The new solution of brick infills intend to represent an enhancement of the seismic performance of this constructive element. The numerical simulation is based on an innovative discrete macro-modelling strategy proposed by Caliò and Pantò (2014). This method is based on a hybrid approach by which the frame is modelled using concentrated plasticity beam-column elements, whereas the non-linear behaviour of masonry infill is modelled by means of a 3D discrete macro-element. The main goals of this work are: (1) to calibrate a numerical model based on the experimental results of the out-of-plane tests on two types of brick masonry infill walls; (2) to assess the efficiency of the macro-modelling approach by comparing the numerical results; (3) to assess the main influencing material and geometric parameters in the out-of-plane behavior of brick infill walls. The results of the numerical simulation enabled to assess the good performance of the macro-modelling approach in simulating the seismic response of brick infill walls and predicting the failure mechanisms. In addition, it was possible to identify the main influencing parameters in the out-of-plane behavior of brick infill walls.